Demonstrating why DFT-calculations for molecular transport in solvents need scissor corrections - Bâldea, Ioan (Electrochemistry communications, 2013)
With the aid of two typical molecules [(4, 4′)-bipyridine and octanedithiol], often used to fabricate nanoelectronic devices, we demonstrate why DFT calculations for the transport in single-molecule junctions immersed in solvents are not only quantitatively but also qualitatively inappropriate, (ii) why, in order to obtain meaningful results, scissor corrections are needed, and (iii) that scissor corrections can be deduced by quantum chemical calculations that can obviate the explicit treatment the atomistic structure of the solvent.
Gesehen am 01.12.2020